BS EN 4641-102. Aerospace series. Cables, optical 125 μm outside diameter cladding. Part 102. Semi-loose 62, 5/125 μm GI fibre nominal 1, 8 mm outside diameter. Product standard (19th November 2019) - British Standards Institution,
No abstract available